Generalist in allogeneic hematopoietic stem cell transplantation for MDS or AML: Epigenetic therapy - Yang, Guancui; Wang, Xiang; Huang, Shiqin; Huang, Ruihao; Wei, Jin; Wang, Xiaoqi; Zhang, Xi (Frontiers in Immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the only curative treatment for patients with myeloid malignancies such as myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). However, relapse and graft-versus-host disease (GvHD) still affect the survival of patients who receive allo-HSCT, and more appropriate therapeutic strategies should be applied at all stages of transplantation to prevent these adverse events. The use of epigenetics agents, such as hypomethylating agents (HMAs), has been explored to decrease the risk of relapse by epigenetic modulation, which is especially effective among AML patients with poor mutations in epigenetic regulators. Furthermore, epigenetic agents have also been regarded as prophylactic methods for GvHD management without abrogating graft versus leukemia (GvL) effects. Therefore, the combination of epigenetic therapy and HSCT may optimize the transplantation process and prevent treatment failure. Existing studies have investigated the feasibility and effectiveness of using HMAs in the pretransplant, transplant and posttransplant stages among MDS and AML patients. This review examines the application of HMAs as a bridge treatment to reduce the tumor burden and the determine appropriate dose during allo-HSCT. Within this review, we also examine the efficacy and safety of HMAs alone or HMA-based strategies in posttransplant settings for MDS and AML. Finally, we provide an overview of other epigenetic candidates, which have been discussed in the nontransplant setting.